2010
DOI: 10.1260/1747-9541.5.3.425
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Coach Leadership Models to Coaching Practice: Current State and Future Directions

Abstract: The purpose of this concept/review article is to critically discuss the application of sports coaching leadership models to coaching practice. The focus of the discussion will be on the coherence and impact of the numerous models in the current literature, and the accumulated impact that they have on practitioners. This discussion will be framed in current conceptions of sports coaching and expected athlete outcomes. This article can serve an important role in the continuing dialogue about the essence of sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
1
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 39 publications
0
52
1
9
Order By: Relevance
“…In this way, any data produced using the LSS "must be examined with caution" (Becker, 2009, p. 94) when applying to a sports coaching context. Vella, Oades, and Crowe (2010) agree, arguing that quantitative measures of leadership have had little impact on coaching because practitioners do not value such models as much. This may be because measures have not been generated for immediate use for coaches (Vella et al, 2010).…”
Section: Understanding Athlete Preferences: Privileging the Voices Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…In this way, any data produced using the LSS "must be examined with caution" (Becker, 2009, p. 94) when applying to a sports coaching context. Vella, Oades, and Crowe (2010) agree, arguing that quantitative measures of leadership have had little impact on coaching because practitioners do not value such models as much. This may be because measures have not been generated for immediate use for coaches (Vella et al, 2010).…”
Section: Understanding Athlete Preferences: Privileging the Voices Ofmentioning
confidence: 99%
“…Vella, Oades, and Crowe (2010) agree, arguing that quantitative measures of leadership have had little impact on coaching because practitioners do not value such models as much. This may be because measures have not been generated for immediate use for coaches (Vella et al, 2010). Similarly the Coach Evaluation Questionnaire (CEQ) (Rushall & Wiznuk, 1985) was not devised using the perceptions of athletes or coaches even though the constructs included in the measure are more relevant to the coaching context.…”
Section: Understanding Athlete Preferences: Privileging the Voices Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Unique components such as inspirational motivation and intellectual stimulation are important because youth sports are expounded as appropriate avenues for youth development due to simultaneously high levels of attention, motivation and challenge [22]. Further, components such as individual consideration and fostering acceptance of group goals speak to the inherent nature of coaching practice as constituted by the relationship between coach and athlete [23], which itself is set amongst the context of the multiple interpersonal relationships. The importance of these components are highlighted by research that has shown that the personal experience of effective coaching is predominantly about the relationships and environment that the coach creates rather than a limited range of prescribed behaviours [24].…”
Section: Introductionmentioning
confidence: 99%